Studi Empiris Terkait Dengan Pengungkapan Sukarela, Kualitas Audit Dan Asimetri Informasi Terhadap Stock Return Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia - Jenny Sihombing; Sukrisno Agoes; Urip Santoso (Jurnal Akuntansi, 2017)
This study used data of manufacturing companies listed on the Jakarta StockExchange (JSX) as unit of analysis. The purpose of this study is to find out the influenceof voluntary disclosures and audit quality on information asymmetry. This study also aimsto determine the effect of voluntary disclosure, audit quality and information asymmetryon stock return. In addition, this study aims to find out the ability of informationasymmetry to mediate the effect of voluntary disclosure and audit quality on informationasymmetry.This research used verificative-descriptive methodwith quantitative approach.The analytical method used in statistical data processing was path analysis. There are 132manufacturing companies listed on JSX became the research samples of this study.Thetesting results shows that there are significant impact of voluntary disclosure and auditquality on information asymmetry. The testing results also show that there are significantimpact of voluntary disclosure and information asymmetry on stock return, while the auditquality has no significant impact on stock return. At the same time, informationasymmetry is significant to be the mediating variable on the impact of voluntarydisclosure and audit quality towards stock return.Voluntary disclosure, audit quality andinformation asymmetry can be the determinant variables onStock Returnofmanufacturing companies, listed on JSX.